A second major histocompatibility complex susceptibility locus for multiple sclerosis - Yeo, Tai Wai; De Jager, Philip L.; Gregory, Simon G.; Barcellos, Lisa F.; Walton, Amie; Goris, An; Fenoglio, Chiara; Ban, Maria; Taylor, Craig J.; Goodman, Reyna S.; Walsh, Emily; Wolfish, Cara S.; et al. (Annals of neurology, 2007)
Objective Variation in the major histocompatibility complex (MHC) on chromosome 6p21 is known to influence susceptibility to multiple sclerosis with the strongest effect originating from the HLA‐DRB1 gene in the class II region. The possibility that other genes in the MHC independently influence susceptibility to multiple sclerosis has been suggested but remains unconfirmed. Methods Using a combination of microsatellite, single nucleotide polymorphism, and human leukocyte antigen (HLA) typing, we screened the MHC in trio families looking for evidence of residual association above and beyond that attributable to the established DRB1*1501 risk haplotype. We then refined this analysis by extending the genotyping of classical HLA loci into independent cases and control subjects. Results Screening confirmed the presence of residual association and suggested that this was maximal in the region of the HLA‐C gene. Extending analysis of the classical loci confirmed that this residual association is partly due to allelic heterogeneity at the HLA‐DRB1 locus, but also reflects an independent effect from the HLA‐C gene. Specifically, the HLA‐C*05 allele, or a variant in tight linkage disequilibrium with it, appears to exert a protective effect (p = 3.3 × 10−5). Interpretation Variation in the HLA‐C gene influences susceptibility to multiple sclerosis independently of any effect attributable to the nearby HLA‐DRB1 gene. Ann Neurol 2007